PENGEMBANGAN POTENSI EKSTRAK DAUN PANDAN (Pandanus amaryllifolius Roxb) SEBAGAI AGEN ANTIBAKTERI - Mardiyaningsih, Ana; Aini, Resmi (Universitas Ahmad Dahlan, 2014)
Pandanus amayllifolius Roxb which commonly used as a flavoring and food coloring waspotentially have antibacterial activity. It should be an effort to develop a safe naturalpreservatives to reduce cases of food poisoning (foodborne disease) which mainly caused bybacterial pathogens. This study aims to determine the antibacterial potency of the water extract,ethanol, ethyl acetate, and a mixture of ethanol-ethyl acetate (1:1 v/v) extract againstStaphylococcus aureus and Escherichia coli based on the value of MIC (Minimum InhibitoryConcentration) and MBC (Minimum Batericidal Activity). The antibacterial activity wasevaluated by the Kirby-Bauer diffusion method by making the extract concentration of 25 and50 %, as well as the loading dose tested was 2.5 mg and 5 mg/disc. MIC and MBC wasevaluated by solid dilution method. The results showed that the ethanol extract and water extractdonât have antibacterial activity against Staphylococcus aureus and Escherichia coli, whereasthe ethyl acetate extract and a mixture of ethanol-ethyl acetate (1:1 v/v) have an antibacterialactivity. Ethyl acetate extract showed the highest inhibitory potency. The MIC and MBC was 186 PharmaÒ«iana, Vol. 4, No. 2, 2014: 185-192obtained at a level of 1.1% w/v and 6.7% w/v against Staphylococcus aureus, and 0.5% w/v and4.5% w/v against Escherichia coli.